A brief review of augmented reality science learning - Gopalan, Valarmathie; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir (IP Publishing LLC, 2017)
This paper reviews several literatures concerning the theories and model that could be applied for science motivation for upper secondary school learners (16-17 years old) in order to make the learning experience more amazing and useful. The embedment of AR in science could bring an awe-inspiring transformation on learners’ viewpoint towards the respective subject matters. Augmented Reality is able to present the real and virtual learning experience with the addition of multiple media without replacing the real environment. Due to the unique feature of AR, it attracts the mass attention of researchers to implement AR in science learning. This impressive technology offers learners with the ultimate visualization and provides an astonishing and transparent learning experience by bringing to light the unseen perspective of the learning content. This paper will attract the attention of researchers in the related field as well as academicians in the related discipline. This paper aims to propose several related theoretical guidance that could be applied in science motivation to transform the learning in an effective way.